(untitled) (Prithvi Academic Journal, 2025)
Based on the critical review of some of the existing literature on urbanization, urbanism and urban identity by pioneering figures in urban anthropology and sociology, I have attempted to discover if there exists any universal set of characteristics by which the urban identity of a person can be explained. I have supplemented my critical review with some of the useful empirical evidences from my fieldwork undertaken in the city of Butwal, Nepal. Scholars such as Simmel, Wirth and others have been found to be outlining some of the elements of urbanism, urban identity and urban social relations that can be universally applicable. However, their formulations have been criticized by succeeding scholars, especially from anthropology and sociology, by stressing that it is almost impossible to delineate universally applicable set of characteristics of urban identity. Thus, I conclude that some commonalities may exist among the urban dwellers of different cities or urban context across the globe, but there exist no such universal set of elements of urban identity of an urban dweller.